MODERN SCIENTIFIC AND METHODOLOGICAL APPROACHES TO THE MANAGEMENT OF INDUSTRIAL ENTERPRISES - S. Logvinov (Вестник университета)
The article discusses issues related to the analysis of various scientific and methodological approaches to the management of industrial enterprises in domestic and foreign practice. Special attention is paid to modern scientific philosophies for the effective management of industrial enterprises.